Understanding the Ligand‐Directed Assembly of a Hexanuclear ThIV Molecular Cluster in Aqueous Solution. Issue 24 (19th July 2013) - Hu, Yung‐Jin; Knope, Karah E.; Skanthakumar, S.; Soderholm, L.
Abstract: The electrochemical hydrolysis of thorium(IV) was monitored by a combination of high‐energy X‐ray scattering (HEXS) and NMR spectroscopy. Once formed, μ2 ‐dihydroxo‐bridged dimers remain stable in solutions of moderate pH until glycine is added, upon which the dimers rapidly condense to form hexanuclear clusters [Th6 (μ3 ‐O)4 (μ3 ‐OH)4 ] 12+ . In the absence of the dimers or glycine, the clusters do not form even if the solutions are stored over extended times. Abstract : The assembly of a [Th6 (μ3 ‐O)4 (μ3 ‐OH)4 ] 12+ cluster in aqueous solution was studied by using in situ high‐energy X‐ray scattering (HEXS) and NMR spectroscopy. The hexamer structure, typical of that of hydrolyzed tetravalent cations, is formed quantitatively by the assembly of pre‐existing μ2 ‐OH‐bridged Th IV dimers upon the addition of glycine. Both the dimers and the glycine are necessary for assembly of the hexamer.